Beyond adoption: Welfare effects of farmer innovation behavior in Ghana - Justice A. Tambo; Tobias Wünscher (University of Bonn, Center for Development Research (ZEF), 2016)
With numerous challenges hindering smallholders' adoption of externally developed technologies, it is often argued that farmer innovation can play an essential role in rural livelihoods. Yet a rigorous assessment of the impact of farmer innovation is lacking. We address this issue by analyzing the effect of farmer innovation on household welfare, measured by income, consumption expenditure, and food security. Using household survey data from northern Ghana and applying endogenous switching regression, we find that farmer innovation significantly increases household income and consumption expenditure for innovators. It also contributes significantly to the reduction of food insecurity among innovative households by increasing household food consumption expenditure, decreasing the duration of food shortage, and reducing the severity of hunger. However, we find that the positive productivity and income effects of farmer innovation do not significantly translate into nutritious diet, measured by household dietary diversity. Overall, our results show positive welfare effects of farmer innovation, hence, support increasing arguments on the need to promote farmer innovation (which has been largely undervalued) as a complement to externally promoted technologies in food security and poverty reduction efforts.
Keywords: D13; O31; Q12; Q16; 330; farmer innovation; household welfare; impact assessment; endogenous switching regression; Ghana